2017
DOI: 10.1038/s41467-017-00108-3
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate genome-wide association meta-analysis of pediatric musculoskeletal traits reveals pleiotropic effects at the SREBF1/TOM1L2 locus

Abstract: Bone mineral density is known to be a heritable, polygenic trait whereas genetic variants contributing to lean mass variation remain largely unknown. We estimated the shared SNP heritability and performed a bivariate GWAS meta-analysis of total-body lean mass (TB-LM) and total-body less head bone mineral density (TBLH-BMD) regions in 10,414 children. The estimated SNP heritability is 43% (95% CI: 34-52%) for TBLH-BMD, and 39% (95% CI: 30-48%) for TB-LM, with a shared genetic component of 43% (95% CI: 29-56%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 69 publications
(91 reference statements)
8
71
0
3
Order By: Relevance
“…Of the above identified loci, 17 were reported by GWAS or meta-analysis of DXA-derived lean mass [13, 15, 19]; 104 were reported by a study of electronic impedance measured lean mass in a subset UKB cohort subjects (N=155,961) [20].…”
Section: Resultsmentioning
confidence: 99%
“…Of the above identified loci, 17 were reported by GWAS or meta-analysis of DXA-derived lean mass [13, 15, 19]; 104 were reported by a study of electronic impedance measured lean mass in a subset UKB cohort subjects (N=155,961) [20].…”
Section: Resultsmentioning
confidence: 99%
“…According to the analysis of GO, KEGG and individual gene function, we subsequently put our interest in exercise-related genes of Abaga horse. Twenty-one genes may involve in exercise of Abaga horse while their functions embodied vasoconstriction ( HTR2B ) (Launay et al 2002; Bevilacqua et al 2010; Meira et al 2014), angiogenesis ( CDH5 ) (Sauteur et al 2014), cardiac contraction ( KCNQ1 ) (Jespersen et al 2005; Brown et al 2015; Pedersen et al 2017), cardiac development and muscle structure ( ENAH ) (Franzini-Armstrong 1973; Benz et al 2013), muscle growth ( PIH1D1, SMURF1 ) (Inoue et al 2010; Ponsuksili et al 2014; Dalbo et al 2013), myogenic differentiation ( UNC13C ) (Meyer et al 2015; Langlois and Cowan 2017), skeletal muscle function ( ATP1A3 ) (Aughey et al 2007; Brashear et al 2007), femur strength and bone mineral density ( PPP2R5B, PPP6R3 ) (Alam et al 2009; Medina-Gomez et al 2017), osteoclast growth ( PTPRE, RHOBTB1 ) (Chiusaroli et al 2004; Song et al 2014), chondrogenesis (SCFD) (DeLise et al 2000; Hou et al 2017), lipid and carbohydrate metabolism ( PPARD, GCG, TCF7L2, GALNT13 ) (Yi et al 2005; Bevilacqua et al 2010; Park et al 2012; Ahmetov and Fedotovskaya 2015; Giordano Attianese and Desvergne 2015; Ropka-Molik et al 2017), exercise stress-induced response ( CD69, EIF4G3 ) (Testi et al 1989; Gradi et al 1998; Cappelli et al 2007; Morabito et al 2016), exercise coordination ( GRM1 ) (Conquet et al 1994; Bossi et al 2017) and height ( VGLL4 ) (Gabriel et al 2016). These genes of positive selection were presented simultaneously in Abaga horse, which may be a reason that it runs rapider than Wushen horse.…”
Section: Resultsmentioning
confidence: 99%
“…We found several genes associated with skeleton and cartilage development among candidate genes of Abaga horse. PPP2R5B and PPP6R3 are closely related to femur strength in rats and bone mineral density in humans, respectively (Alam et al 2009; Medina-Gomez et al 2017). PTPRE encodes receptor-type tyrosine-protein phosphatase epsilon which is a positive regulator of osteoclast function (Chiusaroli et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…For example, myostatin ( GDF8 ) knockout mice weigh more and have significantly larger muscles and higher bone density than wild‐type mice . In addition, bivariate genome‐wide association studies found pleiotropic impacts on total‐body lean mass and total‐body‐less‐head BMD at the SREBF1/TOM1L2 locus in children, an effect mostly likely mediated by SREBF1 …”
Section: Topic 2: Epidemiology and Clinical Measuresmentioning
confidence: 99%
“…28 In addition, bivariate genome-wide association studies found pleiotropic impacts on total-body lean mass and total-body-less-head BMD at the SREBF1/TOM1L2 locus in children, an effect mostly likely mediated by SREBF1. 29 Other research is addressing the need for better markers of osteoporosis and sarcopenia. The markers used in clinical trials include serum procollagen type 1 aminoterminal propeptide and serum C-terminal crosslinked telopeptide of type I collagen, but their utility in clinical practice is unclear.…”
Section: Topic 2: Epidemiology and Clinical Measuresmentioning
confidence: 99%